The role of tachycardia and beta-adrenergic stimulation in inducing early cardiac remodelling. (10th June 2022) - Kiessling, M; Djalinac, N; Matzer, I; Voglhuber, J; Ljubojevic-Holzer, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): BioTechMed Graz Objective: Cardiac remodelling encompasses changes at the molecular, cellular and gene expression level following pathologic insult to the heart. Initially, it maintains cardiovascular homeostasis and allows patients to remain asymptomatic, but if untreated, it eventually progresses to symptomatic heart failure. Excessive β-adrenergic stimulation and tachycardia are potent triggers of cardiac remodelling; however, the underlying mechanisms of their cellular effects are not fully understood. Using neonatal rat ventricular cardiac myocytes (NRVCMs), we studied individual and synergistic potency of ß-adrenergic stimulation and tachycardia to modulate pathological gene expression profiles, as well as the effectiveness of ß-blockers (BB) in preventing these alterations. Methods: Primary NRVCMs were isolated from 1-day-old neonatal Wistar rats, cultured for 3 days and subsequently stimulated for 3h at basal (1Hz) and tachycardia (8Hz) conditions either in (1) cell culture medium to determine the sole effect of tachycardia, (2) cell culture medium supplemented with ß-adrenergic agonist isoprenaline (ISO; 10µM) to investigate the influence of ß-adrenergic stimulation and signalling or (3) cell culture medium supplemented with ISO following 1h preincubation with propranolol (ISO+BB; 1µM) to assess the potential of BB in preventing gene reprogramming. Screening of relative mRNA levels of hypertrophic marker genes and regulators of ion homeostasis in cardiomyocytes was performed by qPCR and calculated using the 2-ΔΔCt quantification method. Results: qPCR screening of the known hypertrophic marker genes revealed that tachycardia caused significant transcriptional upregulation of regulator of calcineurin 1 (RCAN1) and interleukin-6 receptor (IL6R). Treatment with ISO additionally upregulated RCAN1, while preincubation with BB resulted in a return towards baseline expression of both genes, completely blocking the effects of tachycardia alone or when combined with ISO stimulation. Interestingly, two potassium channel genes, KCNH2 and KCNJ2, responsible for expression of hERG and Kir2.1 channels, respectively, were unchanged with tachycardia alone but significantly downregulated upon additional stimulation with ISO. Preincubation with BB could - at least partially - reverse the effect. Conclusion: In conclusion, we could show that apart from the well-documented effect of excessive ß-adrenergic stimulation on hypertrophic signalling in cardiomyocytes, it also has a direct, non-tachypacing mediated effect on the expression levels of hERG and Kir2.1 potassium channels, which may be causally involved in inducing early cardiac remodelling. Thus, a previously unidentified benefit of BB therapy may be restoring potassium homeostasis contributing to the prevention of adverse cardiac remodelling and its progression to heart failure.